Boredom and affective temperaments as factors hindering smoking cessation: An exploration within an Italian sample - Fiammetta Iannuzzo; Michele La Versa; Fabrizio Turiaco; Gianluca Pandolfo; Carmela Mento; Maria Rosaria Anna Muscatello; Antonio Bruno; Clara Lombardo (AIMS Public Health)
BackgroundSmoking cessation presents challenges influenced by neurological adaptations and psychological factors, potentially exacerbated by susceptibility to boredom and affective temperaments.MethodsThis study enrolled 409 participants via an online survey distributed among the Italian population through mailing lists, social networks, and messaging apps. Specific questions assessed cigarette smoking, while the Temperament Evaluation of Memphis, Pisa, Paris, and San Diego (TEMPS-A) and Boredom Proneness Scale (BPS) explored affective temperaments and susceptibility to boredom, respectively.ResultsResults indicated smokers exhibited higher cyclothymic temperament scores compared to no-smokers and ex-smokers, suggesting a connection between this temperament and smoking behavior. Furthermore, the analysis demonstrated variable influences of specific temperaments on boredom proneness.ConclusionsThese findings emphasize the significance of incorporating affective temperaments and boredom proneness into smoking cessation interventions. Understanding the interplay between affective temperaments and boredom proneness can guide the development of innovative and personalized cessation strategies. Further research is warranted to delve deeper into these relationships and their implications for intervention approaches.